Королева грез моих: [Лирич. песни и стихи, киносценарий] - Высоцкий Владимир Семенович (1993)
Экземпляры: ф.10 (1993) / Инвентарный номер: 37105 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 93 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6